508 Puerperal thrombosis on mitral valve prothesis. (17th January 2020) - Moniz Mendonca, F V; Sousa, J A S; Monteiro, J M; Mraquel, M R; Neto, M N; Caires, G C; Freitas, D F
Abstract: Introduction: Replacement of a diseased heart valve with a prosthetic heart valve exchanges the native disease for prosthesis-related complications. Valve thrombosis can occur in mechanical prosthetic valves. The significant morbidity and mortality associated with this condition permits rapid diagnostic evaluation. A combination of transthoracic and transoesophageal echocardiography (TEE) is required to assess the haemodynamic effect of thrombosis, leaflet motion and thrombus size. Mechanical valves offer excellent haemodynamic performance and long-term durability, but the need for anticoagulation increases maternal and foetal mortality and morbidity, and the risk of major cardiac events during pregnancy. Case report: A 23-year-old gravida 0 woman was admitted to the emergency obstetric care. At the age of 18 months, she underwent valve replacement surgery in the mitral position (St. Jude Medical Standard size 25mm), this requires use of warfarin after surgery. Although she was advised otherwise; the patient became pregnant. She had an increased risk of maternal cardiovascular complications [Modified World Health Organization classification (mWHO) III] and obstetrics complications. The warfarin treatment was discontinued, and it was started low molecular weight heparin (LMWH) 100IU, twice daily subcutaneously, on gestation 36 week. The last administration was 2 days before the admission (>48h before delivery). So, on gestation week 39, she was admitted to the department of Obstetrics. Then, as cardiotocography showed decreased foetal heart rate, an emergency caesarean section was performed. A healthy baby was delivered. After delivery, we perform an immediate two-dimensional transthoracic echocardiography (2D TTE), as there was a high-risk of valve thrombosis, and it showed an apparent normal prosthetic excursion but a high mean pressure gradient (25mmHg) – elevated transprosthetic gradient. It was not well visualized the occlude motion of the mechanical valve by 2D TTE, so we perform a TEE to answer the clinical question, if there was a dysfunction due to an acute process (i.e. thrombus). It revealed an obstruction – reduced mobility of one disc and elevated velocities by CW doppler (30mmHg), and a presence of thrombus (1.3X0.8mm). The anticoagulation with intravenous UFH was started immediately, but anticoagulation failed, and she underwent valve replacement surgery (St. Jude Medical standard size 27mm. Conclusion: Our patient had a very-high risk of complications maternal cardiovascular complications - WHO risk classification III - because the risk of valve thrombosis is markedly increased during pregnancy. The risk is lower with adequate dosing of anticoagulant therapy, but our patient was not which increased the risk of thrombosis. Finally, it is important to notice that it is recommended to manage pregnancy in women with mechanical valves in a centre with a pregnancy heart team.